2023
DOI: 10.3389/fnins.2023.1123784
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of p21-activated kinase-associated neurodevelopmental disorders: From genotype to phenotype

Abstract: Although the identification of numerous genes involved in neurodevelopmental disorders (NDDs) has reshaped our understanding of their etiology, there are still major obstacles in the way of developing therapeutic solutions for intellectual disability (ID) and other NDDs. These include extensive clinical and genetic heterogeneity, rarity of recurrent pathogenic variants, and comorbidity with other psychiatric traits. Moreover, a large intragenic mutational landscape is at play in some NDDs, leading to a broad r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 234 publications
0
4
0
Order By: Relevance
“…As mentioned in the introduction, Rac1 signaling mediates various cellular processes through a wide range of downstream effectors. Historically, the characterization of actin reorganization by Rac1-PAK signaling has been well established [34], which has brought some mechanistic insights into AD pathogenesis, especially spine dysfunction [5,6]. Rac1 is also known to activate PI3K-AKT signaling downstream of GPCR [14], and recent findings show that its activation facilitates cell survival in various cell types [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, Rac1 signaling mediates various cellular processes through a wide range of downstream effectors. Historically, the characterization of actin reorganization by Rac1-PAK signaling has been well established [34], which has brought some mechanistic insights into AD pathogenesis, especially spine dysfunction [5,6]. Rac1 is also known to activate PI3K-AKT signaling downstream of GPCR [14], and recent findings show that its activation facilitates cell survival in various cell types [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Rac1, a member of the Rho-family GTPases, is an intracellular transducer known to control a wide variety of signaling pathways that are critical for cellular processes, including actin reorganization, gene expression, cell viability, and cognitive functions [1][2][3][4]. Emerging evidence indicates that dysfunctional Rac1 signaling is associated with Alzheimer's disease (AD) [5,6]. Rac1 cycles between an inactive GDP-bound form and an activated GTP-bound form in response to extracellular stimuli, including G protein-coupled receptors (GPCRs) and growth factor receptors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified several heterozygous de novo Pak1 mutations, predicted to be gain-of-function mutations, in children with neurodevelopmental abnormalities (developmental delay, postnatal macrocephaly, intellectual disability, autism spectrum disorders, epilepsy, etc.) (Dobrigna et al, 2023;Horn et al, 2019;Kernohan et al, 2019;Ohori et al, 2020;Scorrano et al, 2023). Interestingly, some of these patients show subcortical white matter hyperintensities on magnetic resonance imaging, which may suggest a myelination defect (Horn et al, 2019;Kernohan et al, 2019;Ohori et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Genomic studies in patients with autism spectrum disorders, epilepsy or intellectual deficiency have identified pathogenic mutations in multiple Rho GTPases-encoding genes, but also in various Rho GTPase regulators and effectors ( RAC1, CDC42, PAK ; Michaud et al, 2014 ; Tastet et al, 2019 ; Barbosa et al, 2020 ; Halder et al, 2022 ; Dobrigna et al, 2023 ). Deregulation of Rho GTPases thus seems to be a shared molecular mechanism between several monogenic forms of neurodevelopmental disorders.…”
Section: Cell-intrinsic Regulation Of Cin Migration Dynamicsmentioning
confidence: 99%